Suprascapular ligament ossification and nerve entrapment in a modern skeleton from the central coast of Patagonia, Southern South America - Suby, Jorge Alejandro (2017)
Modification of the suprascapular notch into a foramen as a consequence of the ossification of the suprascapular transverse ligament is a well-known anatomical change. However, it was rarely considered by research in skeletal and cadaveric remains as a possible cause of Suprascapular Nerve Entrapment, a neuropathy that usually produces pain and weakness of the affected shoulder. This paper has the aim to present and to discuss a case of ossification of the suprascapular transverse ligament in a modern-era, possible archaeological male skeleton of 30-45 years old from the central coast of Patagonia, and a possible development of suprascapular nerve entrapment. Complete bilateral ossification of the superior transverse scapular ligament was identified. As no other morphological, traumatic or neoplastic lesions were found in the scapulae, physical activity is suggested as the cause of the ligament ossification in the skeleton, although epigenetic origin cannot be completely rejected.